Putusan Pengadilan Hubungan Industrial pada Pengadilan Negeri Jakarta Pusat di Masa Pandemi COVID-19 - Sinaga, Haposan Sahala Raja; Tobing, Gindo L (Bacarita Law Journal, 2024)
This research legally analyzes the Industrial Relations Court Decision at the Central Jakarta District Court in Central Jakarta during the COVID-19 Pandemic. The issues that will be examined are reasons for filing a lawsuit for an industrial relations dispute that occurred during the COVID-19 pandemic and the judge's legal considerations in the Industrial Relations Court Decision at the Central Jakarta District Court Number 220/Pdt.Sus-PHI/2021/PN. Jkt.Pst. The research method is based on normative juridical legal research methods with a case approach of the Industrial Relations Court Decision at the Central Jakarta District Court Number 220/Pdt.Sus-PHI/2021/PN. Jkt.Pst Results of the Research: First, the reason for filing a lawsuit for an industrial relations dispute that occurred during the COVID-19 pandemic is seen from the Decision of the Industrial Relations Court at the Central Jakarta District Court with case number 220/Pdt.Sus-PHI/2021/PN.Jkt.Pst dated December 6 2021 is the occurrence of rights disputes and termination of employment due to force majeure conditions, namely the COVID-19 pandemic situation which is based on the issuance of Presidential Decree Number 12 of 2020 concerning the Determination of Non-natural Disasters. The Spread of Corona Virus Disease 2019 as a National Disaster. limiting business activities results in losses for business actors. Second, legal considerations in granting termination of employment based on the efficiency of the COVID-19 Pandemic (force majeure), based on the arguments of the Plaintiff's lawsuit along with evidence and witnesses of the Parties linked to the provisions of Article 45 paragraph (2) of Government Regulation Number 35 of 2021, so that the Panel of Judges assessed is legally grounded, therefore, based on justice and propriety, it is stated that the working relationship between the Plaintiff and the Defendant is terminated due to the efficiency reasons of the COVID-19 Pandemic (Force Majeure).